2023
DOI: 10.1021/acsfoodscitech.3c00248
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization, and Stability of Pickering Emulsions Stabilized by Lentil Protein Isolate–Gum Arabic Conjugate Microgel Particles

Ya-Nan Du,
Ya-Ru Wang,
Qin Yang
et al.

Abstract: A new kind of lentil protein isolate (LPI)–gum Arabic (GA) conjugate was fabricated by a wet-heating Maillard reaction. The LPI-GA conjugate gel was then induced by transglutaminase (TGase) and broken into microgel particles by high pressure homogenization to stabilize the Pickering emulsion. The LPI-GA conjugate had a rough and porous flake microstructure as confirmed by scanning electron microscopy, and the LPI-GA conjugate microgel particles (LGMs) were irregular fragments and possessed good colloidal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This involves exposing the protein to very high or low pH levels and then making adjustments to bring it back to neutral . The pH-shifting has been used to modify many proteins with sound effects, such as soy bean protein, ginkgo seed protein, pea protein, hemp protein, and whey protein. ,, The findings indicated that altering pH-shifting improved the performance of proteins by increasing solubility, water/oil absorption, emulsification, and foaming capabilities . However, this method, using a large number of strong acids or alkali to adjust the pH value, has a low protein extraction rate and high energy consumption and is not friendly to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This involves exposing the protein to very high or low pH levels and then making adjustments to bring it back to neutral . The pH-shifting has been used to modify many proteins with sound effects, such as soy bean protein, ginkgo seed protein, pea protein, hemp protein, and whey protein. ,, The findings indicated that altering pH-shifting improved the performance of proteins by increasing solubility, water/oil absorption, emulsification, and foaming capabilities . However, this method, using a large number of strong acids or alkali to adjust the pH value, has a low protein extraction rate and high energy consumption and is not friendly to the environment.…”
Section: Introductionmentioning
confidence: 99%